Does an introduction of a paid parental leave policy affect maternal labor market outcomes in the short run? Evidence from Australia's paid parental leave scheme - Brittany Bass (IZA Journal of Labor Policy, 2020)
This paper studies how an introduction of paid parental leave (PPL) affects maternal labor market outcomes in the short run. Using a reform in Australia, the PPL scheme, that gave the primary caregiver of a child born or adopted on or after January 1 2011, 672.70 a week for a maximum of 18 weeks, this paper develops theoretical predictions of the effect of PPL on maternal labor market outcomes, and tests these predictions using confidential data from the Australian Pregnancy and Employment Transitions Survey. The theoretical results imply that after the introduction of PPL, hours of work in the pre-birth period should decrease for mothers who will qualify for PPL, and increase for mothers who are attempting to qualify for PPL. Post birth, the theoretical results imply that more mothers are out of work and on leave than would have been in the absence of PPL. The empirical results suggest that the PPL scheme had no significant effect on labor market outcomes pre birth or post birth.
Keywords: J13; J16; J20; 330; paid parental leave; maternity leave; maternal employment